Databases for metabolomics research - Ateşşahin, Dilek Arslan; Durna, Yusuf Muhammed (Nova Science Publishers, Inc., 2023)
All biochemical elements that are part of the metabolism are represented in their entirety as the metabolome. It enables researchers to link the phenotype to the function provided as a whole from the genome and environmental variables. Cellular investigations of different components, e.g., DNA, mRNA, proteins, and their interactions, are now largely complemented with metabolomic research for revealing the function and interactions of individual metabolites. Different repositories for various molecules and molecular pathways are present for researchers. The metabolism itself is a vast network of intricate biochemical interactions, and mathematical models are required for a detailed analysis of particular pathways. Such a complex network of interactions can be better assessed using computational algorithms employing precise mathematical models. Metabolomics is already a noteworthy field in discovering novel therapeutic agents. In response to the increased demand for metabolomics research in various fields, different in silico tools were developed for the integrative analysis of metabolic systems, which have their own algorithms and pipelines for data simulation and evaluation. Some of the noteworthy metabolomic databases and associated software are introduced in this chapter. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Data mining; Database; Metabolite; Metabolome; Metabolomic; Network